RELATIONSHIP BETWEEN INTERNET ADDICTION LEVELS AND ANXIETY LEVELS IN FIRST YEAR UDAYANA UNIVERSITY MEDICAL STUDENTS - Pramudia, Ni Putu Cizya Naryati; Lesmana, Cokorda Bagus Jaya; Aryani, Luh Nyoman Alit; Wardani, Ida Aju Kusuma (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i3.P12, 2025)
First year medical students have the potential to experience internet addiction because they experience a double transition process and face competitive lectures. One of the negative impacts of internet addiction is anxiety. Anxiety will get worse when people with internet addiction do not have access to the internet. The aim of this research was to determine whether there was a relationship between internet addiction levels and anxiety levels in first year medical students at Udayana University. This research used a cross sectional analytical design. The research subjects were 177 active medical students at Udayana University class of 2022, aged 18 – 21 years, and not currently receiving therapy for anxiety or anxiety disorders. Research data was collected online via Google Form. This research found that first year Udayana University medical students were not addicted to the internet (19.2%), mild (49.2%), moderate (30.5%), and severe (1.1%) internet addiction. Analysis of anxiety data found no anxiety (27.7%), mild anxiety (26.0%), moderate anxiety (19.8%), and severe anxiety (26.6%). The Spearman Rank correlative test between internet addiction levels and anxiety levels found p = 0.000. It can be concluded that the majority of students experienced mild internet addiction and severe anxiety. This research also concluded that there was a significant relationship between internet addiction levels and anxiety levels in first year medical students at Udayana University (p = 0.000; < 0.05). Keywords : Internet addiction, Anxiety, Medical students